Il territorio raccontato: la valorizzazione dei ‘luoghi’ di Ignazio Silone come elemento propulsivo di circuiti geoturistici autosostenibili - Colecchia, Annalisa (Scienze del Territorio, 2018)
Literary routes inspired by landscapes can become key elements for a self-sustainable development, they illuminating the collective memory, encouraging grassroots processes of self-organisation, and highlighting the relationships between the growth of place consciousness and the enhancement of local patrimonial resources. A significant experience is “Sentiero Silone”, an excursionist itinerary created in the Sirente-Velino Park in 2015, which links the places described by Ignazio Silone and identified through oral interviews with local communities. Silone’s writings give the elements of landscape with symbolic connotations and social meanings, allowing for a dynamic approach to the economic and social-cultural reality of the past; they integrate written sources, archaeological evidences and environmental indicators outlining the various landscapes in their historical depth. and allowing visitors to build a tangible sensorial experience in situ following the author’s life and his novels’ plots. In the Park sustainable tourism and a holistic reading of territories are expressed in various thematic itineraries with the possibility of intersections, to offer a global overview of how an environment can turn into a territory. Literary representation is one of the guidelines to review and interpret landscapes, in order to define the relationships between the past and the present and to propose future scenarios apt to integrate research, innovation and sustainability.